Residential exposure to petrochemical industrial complexes and the risk of leukemia: A systematic review and exposure-response meta-analysis. (March 2020) - Lin, Cheng-Kuan; Hsu, Yu-Tien; Brown, Kristen D.; Pokharel, Bibhaw; Wei, Yaguang; Chen, Szu-Ta
Abstract: Exposure to chemicals produced by petrochemical industrial complexes (PICs), such as benzene, ionizing radiation, and particulate matters, may contribute to the development of leukemia. However, epidemiological studies showed controversial results. This systematic review and meta-analysis aimed to summarize the association between residential exposure to PICs and the risk of leukemia incidence, focusing on exposure-response effects. We searched PubMed, Embase, Web of Science, and Cochrane Library databases for studies published before September 1st, 2019. Observational studies investigating residential exposure to PICs and the risk of leukemia were included. The outcome of interest was the incidence of leukemia comparing to reference groups. Relative risk (RR) was used as the summary effect measure, synthesized by characteristics of populations, distance to PICs, and calendar time in meta-regression. We identified 7 observational studies, including 2322 leukemia cases and substantial reference groups, in this meta-analysis. Residential exposure to PICs within a maximal 8-km distance had a 36% increased risk of leukemia (pooled RR = 1.36, 95% CI = 1.14–1.62) compared to controls, regardless of sex and age. In terms of leukemia subtypes, residential exposure to PICs was associated with the risks of acute myeloid leukemia (AML, pooled RR = 1.61, 95% CI = 1.12–2.31) and chronic lymphocytic leukemia (CLL, pooled RR = 1.85, 95% CI = 1.11–6.42). In meta-regression, the positive association occurred after 10 years of follow-up with a pooled RRs of 1.21 (95% CI = 1.02–1.44) and then slightly increased to 1.77 (95% CI = 1.35–2.33) at 30 years after follow-up. No effect modification was found by sex, age, and geographic locations. Graphical abstract: Image 1 Highlights: Residential exposure to petrochemical industrial complexes was associated with an increased risk of leukemia. The risk of leukemia differed by subtypes of leukemia, particularly in AML and CLL. The risk of leukemia was found after sufficient years of follow-up and slightly increased onward.